Comprehensive ascertainment of bleeding in patients prescribed different combinations of dual antiplatelet therapy (DAPT) and triple therapy (TT) in the UK: study protocol for three population-based cohort studies emulating 'target trials' (the ADAPTT Study). Issue 6 (4th June 2019) - Pufulete, Maria; Harris, Jessica; Sterne, Jonathan A C; Johnson, Thomas W; Lasserson, Daniel; Mumford, Andrew; Doble, Brett; Wordsworth, Sarah; Benedetto, Umberto; Rogers, Chris A; Loke, Yoon; Pithara, Christalla; et al.
Abstract : Introduction: 'Real world' bleeding in patients exposed to different regimens of dual antiplatelet therapy (DAPT) and triple therapy (TT, DAPT plus an anticoagulant) have a clinical and economic impact but have not been previously quantified. Methods and analysis: We will use linked Clinical Practice Research Datalink (CPRD) and Hospital Episode Statistics (HES) data to assemble populations eligible for three 'target trials' in patient groups: percutaneous coronary intervention (PCI); coronary artery bypass grafting (CABG); conservatively managed (medication only) acute coronary syndrome (ACS). Patients ≥18 years old will be eligible if, in CPRD records, they have: ≥1 year of data before the index event; no prescription for DAPT or anticoagulants in the preceding 3 months; a prescription for aspirin or DAPT within 2 months after discharge from the index event. The primary outcome will be any bleeding event (CPRD or HES) up to 12 months after the index event. We will estimate adjusted HR for time to first bleeding event comparing: aspirin and clopidogrel (reference) versus aspirin and prasugrel or aspirin and ticagrelor after PCI; and aspirin (reference) versus aspirin and clopidogrel after CABG and ACS. We will describe rates of bleeding in patients prescribed TT (DAPT plus an anticoagulant). Potential confounders will be identified systematically using literature review, semistructured interviews with clinicians and a short survey of clinicians. We will conduct sensitivity analyses addressing the robustness of results to the study's main limitation—that we will not be able to identify the intervention group for patients whose bleeding event occurs before a DAPT prescription in CPRD. Ethics and dissemination: This protocol was approved by the Independent Scientific Advisory Committee for the UK Medicines and Healthcare Products Regulatory Agency Database Research (protocol 16_126R) and the South West Cornwall and Plymouth Research Ethics Committee (17/SW/0092). The findings will be presented in peer-reviewed journals, lay summaries and briefing papers to commissioners/other stakeholders. Trial registration number: 76607611; Pre-results.